Contemporary Social Work practice and education: A call for a reexamination - Martínez-Brawley, Emilia; Zorita, Paz M-B. (Cuadernos de Trabajo Social, 2016)
In this paper, we will suggest that social work needs to recover its connection to the Aristotelian ethical tradition wherein, to be “virtuous” is a “practice”. Virtue ethics, we argue, is holistic. It implies a strength of character within the polity. No one can live a good life by focusing only on a single “virtue” or dimension of character. Social work is complex a practice through which not only the client but the practitioner will be enhanced or transformed. In spite of the Kantian emphasis on duty, the behaviorists emphasis on “behavior”, the professional associations emphasis on “codes” to control misconduct, and more recently the emphasis on risk management in social agencies, social work is still a “calling” , a moral enterprise wherein excellence depends on the character traits or virtues of the practitioner. The article suggests paths for incorporating virtue ethics in the curriculum.